Discurso, mídia e manifestações culturais: o ethos da segregação na "cidade mais branca do Brasil" - Schmitt, Briane (2019)
The work entitled Discourse, media and cultural manifestations: the ethos of segregation in the “whiter city of Brazil” brings up issues related to the construction of the people culture and identity through their discourse and the way this cultural “image” may be distorted when conveyed by the media. Thus, the general objective of this research is to analyze the construction of ethos in the resident discourses of the city Cunhataí as materiality conveyed by UOL TAB in the report A city of whites. This study is justified because shows associations between the ways a people communicate and the impact of this process on their own culture and identity construction and propagation. For this work to become possible, the theoretical assumptions that support the analysis are based on the postulations of Dominique Maingueneau (1997, 2002, 2005, 2008a, 2008b, 2010a, 2010b) around discourse analysis, more specifically with regard to the notions of scenography and discursive ethos. In addition, considerations around cultural and identity studies are presented from the studies of Clifford Geertz (2015), Stuart Hall (2006) and Kathryn Woodward (2011). The research corpus is composed of a report produced and broadcast by the online channel UOL TAB, it has about three minutes, and it is entitled A City of Whites. The research is characterized as exploratory-descriptive as to objectives, bibliographic and documentary as to procedures and its approach is qualitative. The conclusion of this work is that the projected ethos in the discourse of the report A city of whites is an ethos of opposition and detachment from any representation of blacks and that this image of itself was idealized mainly by the enunciative plan referring to the report as a finished product, whose discourse operated as a simulacrum of the discursive manifestations of the Cunhataí residents participants of the report.